How Hanafism Came to Originate in Kufa and Traditionalism in Medina - Melchert, Christopher (Islamic law and society, 1999)
Abstract The Hanafī and Mālikī personal schools of law are said to have derived from the earlier Kufan and Medinese regional schools. The regional stage of developing Mālikī jurisprudence is plain in works such as the Mudawwana, but early Hanafī works are already focused on Abū Hanīfa and his disciples, so that a regional stage is hard to make out. The biographical dictionaries of Khalīfa ibn Khayyāt and Ibn Sa'd show that there were active traditionists in Kufa equally with the Hijaz. Moreover, the Tabaqāt of Ibn Sa'd shows that he considered the Hanafī school Baghdadi, not Kufan.Kitāb al-Ma'rifa wa-al-tārīkh of Fasawī shows that the Kufan background to Hanafī jurisprudence, together more generally with the identification of Kufa with ra'y and Medina with hadīth, emerged only later in the ninth century.